2023
DOI: 10.3390/biom13121804
|View full text |Cite
|
Sign up to set email alerts
|

The Promoting Mechanism of the Sterile Fermentation Filtrate of Serratia odorifera on Hypsizygus marmoreus by Means of Metabolomics Analysis

Jixuan Cao,
Jiacheng Xie,
Mingming Yu
et al.

Abstract: Hypsizygus marmoreus has become one of the most popular edible mushrooms due to its high nutritional and economic value. Previous researchers found that Serratia odorifera could promote the growth of H. marmoreus by producing and secreting some of its inducers. However, the specific mechanism of action was still unclear. In this study, we found that the exogenous addition of sterile fermentation filtrate (HZSO-1), quorum sensing (QS) signaling molecules, 3-oxo-C6-HSL, cyclo(Pro-Leu), and cyclo(Tyr-Leu) could s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…was reported to show poor antimicrobial activity [96]. It was reported that at an optimal concentration of 10 µg/mL, cyclo-(Tyr-Leu) was able to enhance the mycelial growth of H. marmoreus [97]. It was reported that N-phenethylacetamide hindered the TGF-β/Smad pathway, restraining the metastasis of A549 cells by impacting TGF-β-induced epithelial-mesenchymal transition (EMT) [98].…”
Section: Discussionmentioning
confidence: 99%
“…was reported to show poor antimicrobial activity [96]. It was reported that at an optimal concentration of 10 µg/mL, cyclo-(Tyr-Leu) was able to enhance the mycelial growth of H. marmoreus [97]. It was reported that N-phenethylacetamide hindered the TGF-β/Smad pathway, restraining the metastasis of A549 cells by impacting TGF-β-induced epithelial-mesenchymal transition (EMT) [98].…”
Section: Discussionmentioning
confidence: 99%